1988
DOI: 10.1080/00039896.1988.9934369
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms and Air Pollution Changes in Children: The Gardanne Coal-Basin Study

Abstract: The influence of daily changes in sulfur dioxide (SO2) levels on the induction of respiratory symptoms was studied during the 1983-1984 winter in 450 children, aged 9 to 11 yr, living in the Gardanne coal-basin, France. In this area, SO2 originates mainly from a coal-fueled power plant. The mean SO2 level during the winter was 22 micrograms/m3 in low-pollution areas and 93 micrograms/m3 in polluted areas, with daily SO2 levels up to 356 micrograms/m3. Children completed a daily diary about respiratory symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
2
16
2
1
Order By: Relevance
“…Dodge et al (31) found evidence that respiratory symptoms in children were related to SO2 pollution levels; the same was true in Charpin's study (18 (34) showed that there was no association between NO2 levels in the home and the occurrence of respiratory infections. There was no passive tobacco smoke exposure.…”
Section: Increase In Respiratory Symptoms Survey Datamentioning
confidence: 57%
“…Dodge et al (31) found evidence that respiratory symptoms in children were related to SO2 pollution levels; the same was true in Charpin's study (18 (34) showed that there was no association between NO2 levels in the home and the occurrence of respiratory infections. There was no passive tobacco smoke exposure.…”
Section: Increase In Respiratory Symptoms Survey Datamentioning
confidence: 57%
“…Associations of respiratory and other symptoms with daily levels of SO2 were found in the more polluted communities but not in the less polluted ones (21).…”
Section: Pand Studesmentioning
confidence: 95%
“…Os autores concluíram, então, que, após controle das variáveis socio-econômicas e ambientais, as diferenças entre as crianças da área poluída e da área limpa, evidentes na primeira etapa do estudo, haviam desaparecido com a queda dos níveis de poluição, sugerindo que os efeitos danosos dos poluentes para as vias aéreas eram reversíveis, ao menos naquela faixa etária. Charpin et al (1988) estudaram a sintomatologia respiratória de crianças entre 9 e 11 anos, residentes próximas a uma mina e uma usina de carvão no sul da França e compararam a freqüência de queixas respiratórias entre moradores submetidos a diferentes concentrações de poluentes, particularmente dióxido de enxofre (SO 2 ). Nas áreas poluídas, verificou-se associação significativa entre os níveis de SO 2 e sintomas respiratórios altos e baixos.…”
Section: Os óXidos De Nitrogêniounclassified